Development of a technique for high pressure neutron diffraction at 40 GPa with a Paris-Edinburgh press. Issue 3 (3rd July 2019) - Hattori, T.; Sano-Furukawa, A.; Machida, S.; Abe, J.; Funakoshi, K.; Arima, H.; Okazaki, N.
ABSTRACT: We have developed a technique for neutron diffraction experiments at pressures up to 40 GPa using a Paris-Edinburgh press at the PLANET beamline in J-PARC. To increase the maximum accessible pressure, the diameter of the dimple for sample chamber at the top of the sintered diamond anvils is sequentially reduced from 4.0 mm to 1.0 mm. As a result, the maximum pressure increased and finally reached 40 GPa. By combining this technique with the beam optics which defines the gauge volume, diffraction patterns sufficient for full-structure refinements are obtainable at such pressures.